Prevalence of and risk factors for cutaneous leishmaniasis in East Africa: a systematic review and meta-analysis - Ahmed, Mohammedjud Hassen; Mengiste, Shegaw Anagaw; Asemahagn, Mulusew Andualem (Frontiers in Tropical Diseases, 2025)
BackgroundCutaneous leishmaniasis (CL) is a neglected skin disease that affects millions of people worldwide. Its visible symptoms and impact on physical appearance can lead to social rejection, stigma, and discrimination for patients with cutaneous leishmaniasis. It is a public health and social problem in East Africa. However, there was no conclusive evidence on the pooled prevalence of cutaneous leishmaniasis in East Africa. Thus, we conducted a systematic review and meta-analysis to examine the current evidence on the burden of cutaneous leishmaniasis in East Africa.ObjectiveThe main purpose of this study was to estimate the pooled prevalence of cutaneous leishmaniasis and its risk factors in East Africa.MethodsThis systematic review and meta-analysis were conducted using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses and Stata software version 17. A forest plot and a random effects model were used to estimate the pooled prevalence of CL with a 95% confidence interval (CI) and heterogeneity of articles, respectively.ResultsA total of 221,365 study participants were included in the review. Based on the results, the forest plot was explained by I2 = 99.99% at p < 0.05. The prevalence of cutaneous leishmaniasis in primary studies ranged from 0.73% to 79.10%. The pooled prevalence of CL in East Africa was found to be 22.57% with a 95% CI (14.36, 30.78). The effect size showed statistically significant subgroup effects for study design, study setting, sample size, clinical forms of CL, year of publication, and study period at p < 0.05 according to the subgroup analyses.Conclusion and recommendationsThe pooled prevalence of cutaneous leishmaniasis in East Africa was high. This underscores the urgent need for targeted public health initiatives to mitigate the impact of this disease on affected populations. Collaborative efforts between governments, health organizations, and communities are crucial for the effective management and control of CL in the East Africa region.Systematic review registrationhttps://www.crd.york.ac.uk, identifier CRD42024576017.